Efektivitas Media Dalam Pembelajaran - Wahyuni, Anjar Sri (STAI Miftahul Ula Nganjuk, 2015)
Abstract: Advances in technology in various fields, for example in communications and information technology at the moment, learning media has a central position in the learning process and not solely aids. The media is an integral part of the learning process. In this process, using instructional media associated with anything that can be done by the media. Instructional media used in learning activities can influence the learning efektitas. At first, learning media only serves as a tool for teachers. Two approaches / models of learning media in the electoral process, namely: selecting the model enclosed and open selection model. Closed election occurs when alternative media has been determined. Open selection model is the inverse of the secret ballot. We are still free to choose any type of media, according to our needs. Alternative media is still wide open. Choose open procedures more flexible in nature, because really we adjust to the needs and conditions.